Enhanced long-term stability of perovskite solar cells using a polymer-nanoparticle composite encapsulation layer - Jung, Youngsoo; Lee, Seongha; Pal, Vishal; Ye, Sangho; Kwon, Giryeong; Lee, Doh-Kwon; Lee, Jung-Kun (Elsevier BV, 2025)
One of the hurdles against the commercialization of perovskite solar cells (PSCs) is their rapid degradation in humid and hot environments. Such weakness imposes limitations on the lifespan and reliability of these devices. In this study, we designed a 3-dimensional interpenetrating network (IPN) structure of poly(methyl methacrylate) - polyurethane (PMMA-PU) mixture. Subsequently, CeO2 nanoparticles were incorporated into the IPN polymer for the encapsulation of PSC devices. Physical entanglement between PMMA and PU forms sturdy IPN polymers, which gradually modifies the mechanical properties of the IPN polymer as a function of the PMMA/PU ratio. This entanglement also reduces the free volume within the polymer and suppresses the transport of water molecules, thereby decreasing the water diffusion coefficient. Moreover, the incorporation of CeO2 nanoparticles into the IPN phase further suppresses water transport. Hydrophobic nanoparticles occupy the available free volume via strong bonding with hydrophobic moieties and minimize the flexibility of the IPN polymer matrix. The IPN-CeO2 composite was coated on the PSC and PSC-Si tandem solar cells, and the long-term stability of the devices was tested at 85 degrees C - 85 % relative humidity. The power conversion efficiency (PCE) of encapsulated PSCs decreased by 18 % during 816-h-long test.